Transition to bioeconomy: Perceptions and behaviors in Central and Eastern Europe - Daniela Paşnicu; Mihaela Ghenţa; Aniela Matei (Amfiteatru Economic Journal, 2019)
The implementation of bio-economy, respectively the transition from a fossil fuel-based development to an economy that uses biological resources and innovation in biological sciences requires the formulation of new strategies and policies focused on comprehensive analyzes. The aim of this study is to contribute to a better understanding of the concept and policies of bioeconomy and to analyze citizens' behaviors and perceptions about the development of bioeconomy in the countries of Central and Eastern Europe. The comparative vision has the role to in identifying differences and similarities between national systems and is captured by applying a cluster analysis. The data are from European official statistics - EUROSTAT, plus data collected under Eurobarometer 88.1, from the European Commission and European Parliament. The analysis of the data shows that there are differences between the countries considered, from the perspective of the socio-economic context and also in terms of behaviors that support the bioeconomy. Further efforts are needed in the development of the bioeconomy to achieve both economic growth and employment opportunities as well as the development of behavior centered on the sustainability and resource efficiency of the resource.
Keywords: J10; D19; O13; 330; bioeconomy; transition; social preference; human behaviour; cluster analysis